2013
DOI: 10.1371/journal.pone.0078636
|View full text |Cite
|
Sign up to set email alerts
|

Muscular and Systemic Correlates of Resistance Training-Induced Muscle Hypertrophy

Abstract: PurposeTo determine relationships between post-exercise changes in systemic [testosterone, growth hormone (GH), insulin like grow factor 1 (IGF-1) and interleukin 6 (IL-6)], or intramuscular [skeletal muscle androgen receptor (AR) protein content and p70S6K phosphorylation status] factors in a moderately-sized cohort of young men exhibiting divergent resistance training-mediated muscle hypertrophy.MethodsTwenty three adult males completed 4 sessions•wk-1 of resistance training for 16 wk. Muscle biopsies were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
6
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(173 citation statements)
references
References 43 publications
10
149
6
8
Order By: Relevance
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…The robust study of individual responses to unilateral upper arm RT by Hubal et al (2005) showed that of 585 subjects, approximately 6 % showed practically no gains in muscle size. Also, other RT studies have reported that, in some subjects, muscle size gains are either minimal or non-existent following a training period Davidsen et al 2011;Raue et al 2012;Mitchell et al 2013;Phillips et al 2013). Similarly to muscle size responses, gains in muscle strength during RT are also highly individual (Hubal et al 2005;Erskine et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction It is well established in the human literature that exercise induces an acute increase in cross-sectional area of the muscles during work (Mitchell et al, 2013) There has been no investigation of changes in back shape that occur subsequent to ridden exercise in sports horses. Recommendations concerning saddle fit are empirical and based on anecdotal information.…”
Section: An Investigation Of Exercise-induced Changes In Equine Back mentioning
confidence: 99%
“…We know that the saddle needs to fit the horse in motion, but there has been no investigation of whether the thoracolumbar region changes in shape in association with exercise or how improper saddle fit may influence potential changes. In man, mean muscle fiber area increases post exercise depending on type and intensity of exercise , trunk versus limb muscles and whether or not blood supply is restricted (Mitchell et al, 2013). The objectives were to quantify acute exercise-induced back shape changes in horses and to describe the association with work quality, saddle fit and rider skill level.…”
Section: An Investigation Of Exercise-induced Changes In Equine Back mentioning
confidence: 99%
“…Additionall , the authors suppositio that i reases i T le els are e ide t follo i g resista e e er ise a d that these i reases i a a oli hor o es are esse tial for us ular adaptatio overlooks some recent compelling evidence to the contrary (Mitchell et al, 2013). In conclusion, we argue the high variability of sal-T and sal-C in controlled laboratory conditions (Hayes et al, 2014) will be greater in an applied setting, such as the present study and recommend that conclusions based on these measures should be made both with caution and with reference to the critical difference in order to contextualize any observations made.…”
Section: Letter To the Editormentioning
confidence: 96%